Policing Women’s Bodies in an Illiberal Society: the Case of Ireland - Quinlan, Christina (Women & criminal justice, 2017)
This journal article outlines the history of the policing women’s bodies in Ireland in the context of law, crime and reproduction. It does this by means of three case studies. The first case study explores the policing of women’s bodies in relation to sexuality. The second case study focuses on reproduction and the policing of women’s bodies in relation to reproduction. The third and final case study considers the policing of women’s bodies in relation to abortion. Taken together, these three case studies provide an overview of the capacity, and indeed the readiness, that exists in Irish society to police women’s bodies and to do so particularly in relation to sexuality and reproduction.